2022
DOI: 10.1021/acs.est.2c01850
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Organophosphate Triesters and Diesters across the Blood–Cerebrospinal Fluid Barrier: Efficiencies, Impact Factors, and Mechanisms

Abstract: The penetration of organophosphate triesters (tri-OPEs) and diesters (di-OPEs) across the blood–brain barrier and their influencing factors remain unclear in humans. In this study, 21 tri-OPEs and 8 di-OPEs were measured in 288 paired serum and cerebrospinal fluid (CSF) samples collected in Jinan, China. Six tri-OPEs were frequently detected in both serum and CSF, with median concentrations ranging from 0.062 to 1.62 and 0.042–1.11 ng/mL, respectively. Their penetration efficiencies across the blood–CSF barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 80 publications
1
13
1
Order By: Relevance
“…We show that the organophosphate flame retardant TDCIPP arrests the development of mouse oligodendrocytes and inhibits oligodendrocyte generation in human cortical organoids at concentrations similar to estimated blood concentrations in children 46 . Our results and the likelihood of organophosphate flame retardant exposure in children raise potential health concerns as these chemicals may reach higher concentrations in cerebrospinal fluid than blood 47 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We show that the organophosphate flame retardant TDCIPP arrests the development of mouse oligodendrocytes and inhibits oligodendrocyte generation in human cortical organoids at concentrations similar to estimated blood concentrations in children 46 . Our results and the likelihood of organophosphate flame retardant exposure in children raise potential health concerns as these chemicals may reach higher concentrations in cerebrospinal fluid than blood 47 .…”
Section: Discussionmentioning
confidence: 83%
“…The pervasive use of organophosphate flame retardants has contaminated the environment and increased human exposure, demonstrated by the detection of these chemicals in human blood, urine, breast milk, and cerebrospinal fluid 44,45 . We show that the organophosphate flame retardant TDCIPP arrests the development of mouse oligodendrocytes and inhibits oligodendrocyte generation in human cortical organoids at concentrations similar to estimated blood concentrations in children 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the appropriate physicochemical properties of TCIPP (i.e., molecular weight of 328 Da, molecular volume of 265 Å 3 /molecule, and lipophilicity log K ow of 2.59) may promote its passive diffusion in blood-rich organs. Moreover, its low binding affinities with efflux transporters, such as P-glycoprotein (−4.9 kcal/mol), may inhibit TCIPP efflux from these organs . These reasons altogether resulted in the accumulation of TCIPP in the human liver and kidney.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, its low binding affinities with efflux transporters, such as Pglycoprotein (−4.9 kcal/mol), may inhibit TCIPP efflux from these organs. 66 These reasons altogether resulted in the accumulation of TCIPP in the human liver and kidney. Similarly, it has been reported that TCIPP can cross the blood−cerebrospinal fluid barrier and accumulate in the cerebrospinal fluid with the highest penetration efficiencies (median = 2.80) among target OPEs 67 .…”
Section: Development Of Pbpk Models and Prediction Of Ope Levels In T...mentioning
confidence: 99%
“…Molecular Docking was widely used for estimating the binding affinities of the chemical transporter for classifying and screening for active ligands of environmental contaminants. Membrane transport proteins in humans are largely composed of two families: ATP binding cassette (ABC) and solute carrier (SLC) transporters. , ABC transporters are active transporters and utilize the energy of ATP binding and hydrolysis to facilitate in- or efflux of their substrates across membranes. On the other hand, SLC transporters utilize ion electrochemical gradients, such as sodium or proton gradients for the uphill transport of the substrates .…”
Section: Methodsmentioning
confidence: 99%